PENINGKATAN KEMAMPUAN ANALISIS POKOK BAHASAN MASALAH EKONOMI DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) SISWA SMA NEGERI 1 BANDONGAN KABUPATEN MAGELANG - Yuniarti, Tri; Hadi, Syamsu (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
This research aims to how the use model problem based learning and whether model problem based learning can improving the analysis ability. The subject of this research is the class X IIS1 SMA N 1 Bandongan Kabupaten Magelang. The background of this research is the lack of improving the analysis ability, more over because the learning method that isused is not appropriateto use the oral speech without variation while the characteris annalistic and aplicatif. This studyis anaction research conducted in two cycles. The research finding showed that the percentage of activity of students in learning cycle I with good category and on cycle II increased with very good category, the percentage of the activity of the teacher in the learning cycle I that good category and on cycle II increased with very good category, the average grade achieved in cycle I with good category and on cycle II the average grade increased with very good category.